The Study of Transgender Students in Boarding School - Dhedchawanagon, Kittiwin; Wiwatwongwana, Rangsima (Scholar: Human Sciences, 2021)
This article is part of a qualitative research. The purpose is to study the problems and challenges faced by transgender students. The research was based on the theory of stigmatization of Link and Phelan (Link & Phelan: 2001) as a framework of this research. The main tool to collect and analyze data was using structured interviews with 3 transgender students in a state school in Chiang Mai who defined themselves as “Tom”. However, this was not a participatory observation, instead observation of social behavior of a group of transgender students who define themselves as “Tom” took place in the school by their teacher. The study showed that transgender students who define themselves as “Tom” faced bullying in the forms of verbal bullying, physically bullying, and Tom hate groups within the school. This made transgender students into the subject of ridicule and being sidelined from the large group activities. Which can lead to severe the depression. This research gathered information about the challenges and consequences that transgender students face. Within such findings proper training is entailed. And clear penalties can be imposed since the school has no policy to prevent bullying of students seen as a transgender yet.